Interrelationship between Growth, Inequality, and Poverty: The Asian Experience - Hyun H. Son (Asian Development Bank (ADB), 2007)
This paper examines the relationships between economic growth, income distribution, and poverty for 17 Asian countries for the period 1981–2001. First, it investigates how much growth is required to offset the adverse effect of an increase in inequality on poverty. This trade-off between inequality and growth is quantified using a tool called the "inequality–growth trade-off index." The trade-off index measures how much growth in mean income or expenditure will be required to offset a 1% increase in inequality, with poverty remaining unchanged. Second, the paper looks into the issue of pro-poor growth. How to generate pro-poor growth is a critical challenge for policymakers concerned with sustainable poverty reduction in developing countries. Pro-poor growth is defined as growth that benefits the poor proportionally more than the nonpoor. By using a measure called the "poverty equivalent growth rate", the paper examines both (i) how growth in mean income (or expenditure) has fared in Asia; and (ii) how the benefits of growth are distrubuted between the poor and the nonpoor.
hdl:11540/1855
Keywords: 330; Wirtschaftswachstum; Verteilungswirkung; Einkommensverteilung; Armut; Asien